Penerapan Nilai Kesadaran dalam Pendidikan Bernilai Di Sekolah Dasar - Marwiyah, Syarifatul; Dasuki, Mohamad In; Zaeni, Ahmad; Fadholi, Amak; Alfiah, Evi Alfiatul (Auladuna: Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
As educators in elementary schools, we need to apply some value concepts that must be learned. Some value concepts that must be applied are the value of life, the value of consciousness, the value of the mind, and the value of the will. The importance of applying the value of Awareness in value education is to help students realize and experience values, contribute, and place them integrally in their whole lives. Not only that, the application of the value of awareness will also spread to the character education of a child. Because of the importance of the value of awareness in value education, it is very important in changing children's behavior for the better and instilling noble moral values. Especially in the midst of the rapid progress of the times. So Education also really needs some application to the value of consciousness.